Выбор способа хирургического лечения паховой грыжи и его роль в профилактике послеоперационных осложнений - Никоненко, А. С.; Завгородний, С. Н.; Русанов, И. В.; Головко, Н. Г.; Клименко, А. В.; Охрименко, Г. И.; Белай, А. И.; Децык, Д. А.; Гайдаржи, Е. И.; Никоненко, Олександр Семенович; Головко, Микола Григорович; Клименко, Андрій Володимирович; et al. (My University, 2011)
The results of treatment are analysed 207 patients with inguinal hernia. Age of patients was from 18 to 80, on the average 52±2,3 years. The plastic arts are executed local fabrics in 109(52,6%) patients. Inguinal hernia repair with the mash of polypropylene maked in 98(47,4%) patients. Bilateral non-permanent inguinal hernia repair executedpolypropylene implantatom 10(10,2%) by a patient. Concerning recurrent inguinalhernia operated 7 patients. In 96% patients were applied periduralanaesthesia. The comparative analysis of complications were conducted at the different methods of inguinal hernia repair, advantages of preperitonealmethods of treatment of inguinal hernia are rotined.
Choice of method of the inguinal hernia repair, as method of prophylaxis of postoperativ complications
Keywords: inguinal hernia; operative treatment; postoperation complications